Final safety and health-related quality of lIfe results of the phase 2/3 Act.In.Sarc study with preoperative NBTXR3 plus radiation therapy versus radiation therapy in locally advanced soft-tissue sarcoma - Bonvalot, Sylvie; Hohenberger, Peter (International journal of radiation oncology, biology, physics, 2022)
Purpose - Act.In.Sarc (NCT02379845) demonstrated that the first-in-class radioenhancer NBTXR3, activated by preoperative radiation therapy (RT), doubled the rate of pathologic complete response after resection compared with preoperative RT alone in adult patients with locally advanced soft tissue sarcoma of the extremity or trunk wall (16.1% vs 7.9%, P = .045), and more patients achieved R0 resections (77.0% vs 64.0%, P = .042). These are the toxicity and health-related quality of life (HRQoL) results. - Methods and Materials - Act.In.Sarc randomized eligible patients 1:1 to either NBTXR3 (single intratumoral injection, volume equivalent to 10% of baseline tumor volume, at 53.3 g/L) activated by external-beam RT (arm A) or external-beam RT alone (arm B) (50 Gy in 25 fractions), followed by surgery in both arms. Here, we report the safety analyses in the all-treated population with a long-term follow-up of at least 2 years, and HRQoL in the intention-to-treat full analysis set. - Results - During the on-treatment period, serious adverse events (SAEs) of all grades related to NBTXR3 occurred in 10.1% (9/89) of patients (arm A), and SAEs related to RT occurred in 5.6% (5/89) (arm A) versus 5.6% (5/90) (arm B); postsurgery hospitalization owing to SAEs occurred in 15.7% (14/89) (arm A) versus 24.4% (22/90) (arm B). During the follow-up period, posttreatment SAEs (regardless of relationship) occurred in 13.5% (12/89) (arm A) versus 24.4% (22/90) (arm B). NBTXR3 did not negatively affect HRQoL; during the follow-up period, there was an improvement in most mean Toronto extremity salvage, EuroQoL 5-dimension (EQ-5D), EQ5D02-EQ visual analog scale, reintegration to normal living index, and musculoskeletal tumor rating scale scores. - Conclusions - NBTXR3 did not negatively affect safety or HRQoL. Long-term safety results reinforce the favorable benefit-risk ratio of NBTXR3 plus RT.
Version of record 21 September 2022
Gesehen am 31.01.2023